The Effect of Internal Meaning on Purchase Decision With Attitude Mediation: A Quantitative Explanatory Study of Brawijaya University Students’ Internal Meaning of BTS Meal Co-Branding Products - Pranata, Riky (Advances in Social Sciences Research Journal, 2022)
This research is a study of the study of internal meaning in the study of marketing communications, based on Osgood’s theory or commonly known as the semantic meaning theory. in Osgood’s theory, the meaning of a person is said to lie in a metamorphosis space which consists of three main dimensions, namely evaluate, activity, and potency. The purpose of this study was to analyze the effect of internal meaning on purchase decisions with Attitude mediation. The research object chosen was the BTS Meal co-branding product, which was the result of a collaboration between McDonald’s and the K-Pop boy band Bangtan Boys (BTS). The research sample used a convenience sampling technique consisting of 100 Brawijaya University students from various faculties. This type of research is quantitative and the method used in this research is a survey. The data analysis method used in this study is Partial Least Square (PLS) with the help of the SmartPLS Version 3 program. The findings of this study revealed that the influence of internal meaning on purchase decision with evaluate indicator through Attitude mediation does not affect purchase decision. The influence of internal meaning on purchase decision with activity indicator through mediation Attitude affects purchase decision. The influence of internal meaning on purchase decision with potency indicator through mediation Attitude affects purchase decision. The results of this study reveal that Attitude affects purchase decision.